Impulsive Responses of Viscoelastic Oscillator - SHIMIZU, Nobuyuki; IIJIMA, Masaki (Transactions of the Japan Society of Mechanical Engineers Series C, 1998)
This paper describes transient impulsive responses of a 1-DOF viscoelastic vibratory system to impulsive excitation. The solutions of the 1-DOF system with viscoelastic material described by the fractional Voigt model of differential order of q being less than unity are examined and classified with the roots of characteristic polynomial of the governing equations of motion. The characteristics of transient impulsive responses of viscoelastic vibratory system against impulsive excitation are analized and compared with those of viscous vibratory system from the viewpoint of shock absorbing property.